Rooting Response in Stem Cuttings of Jatropha gossypifolia - Kumar, R. V.; Swarnkar, Gagan Kumar (Indian Journal of Agroforestry, 2020)
Out of numerous species of Jatropha, J. gossypifolia is of great concern as it has natural proximity to form interspecific hybrid with J. curcas. In the era of search for bio-fuel, research on different aspects is much needed. Vegetative propagation is one of the important means of producing a number of genetically identical individuals. In the present set of experiment, different concentrations of IBA i.e. 25, 50, 75, 100, 125 and 150 (24 hour treatment) and 500, 1000, 1500, 2000, 2500 (3-4 minutes treatment) along with distilled water (control) were tried for vegetative propagation. IBA concentrations of 50 and 75 ppm (24 hour dip) and 1000 and 1500 ppm (3-4 minute dip) was found to be reasonably superior over other treatments in relation to rooting responce, survival of rooted plants and vigour of the plant. However distilled water treatment can serve the purpose for cloning in this species.